INTERVENSI KEPERAWATAN UNTUK MENURUNKAN KECEMASAN ANGGOTA KELUARGA PASIEN SELAMA PERIODE INTRAOPERATIVE - Haura Labibah Salsabil Sulaksono; Reni Sulung Utami (Jurnal Ilmu Keperawatan Medikal Bedah, 2021)
Background: Surgery can cause anxiety of family member because uncertainty during awaiting surgery. Nursing intervention is needed to reduce anxiety of family member during intraoperative period. Objective: To identify strategies or nursing intervention in alleviating anxiety of family member of patient during intraoperative period. Method: This is literature review. Authors search article in electronic database such as SpringerLink, Scopus, EBSCOhost, Semantic Scholar, Portal Garuda and web search engine Google Scholar. The inclusion criteria of article are full text, quantitative research, in English or Indonesian language, year of publication was 2010 – 2020, and article’s topic in accordance with the research problem area. Results: Thirty – four articles were obtained and only nine articles were eligible to be included in this review. The review shows that anxiety level of family member during intraoperative decline after being given an intervention. The nursing intervention are providing information cards, providing information and visiting hours, watching TV, audiovisual orientation, and sending text messages. Conclusion: There are several nursing interventions that can be implemented by nurses to reduce family members’ anxiety during intraoperative period. Providing information to the family is very important and beneficial during intraoperative period.  Latar Belakang: Tindakan pembedahan dapat mengakibatkan kecemasan pada keluarga pasien karena ketidakpastian selama menunggu operasi. Intervensi keperawatan diperlukan untuk menurunkan kecemasan keluarga pasien selama periode intraoperative.  Objektif: Untuk mengidentifikasi strategi atau intervensi keperawatan dalam menurunkan kecemasan keluarga pasien selama periode intraoperative. Metode: Studi ini merupakan literature review. Peneliti melakukan penelusuran artikel secara elektronik melalui SpringerLink, Scopus, EBSCOhost, Semantic Scholar, Portal Garuda dan mesin pencari Google Scholar. Pemilihan artikel ditetapkan berdasarkan kriteria inklusi, yaitu full teks, design penelitian kuantitatif, berbahasa Inggris atau Indonesia, tahun publikasi 2010 – 2020, dan artikel sesuai dengan topik masalah penelitian. Hasil: Sebanyak 34 artikel didapatkan dan 9 artikel yang memenuhi kriteria inklusi. Hasil review menunjukkan rata – rata tingkat kecemasan keluarga pasien mengalami penurunan setelah mendapatkan intervensi keperawatan. Intervensi keperawatan yang dapat menurunkan kecemasan keluarga pasien selama menunggu operasi meliputi pemberian kartu informasi, pemberian informasi dan kunjungan, menonton TV, orientasi audiovisual, dan pengiriman pesan teks. Kesimpulan: Perawat dapat memberikan beberapa bentuk intervensi keperawatan untuk menurunkan kecemasan keluarga pasien selama periode intraoperative. Pemberian informasi kepada keluarga sangat penting dan bermanfaat selama fase intraoperative.